Characterization and identification of Oya virus, a Simbu serogroup virus of the genus Bunyavirus, isolated from a pig suspected of Nipah virus infection - Kono, Y.; Yusnita, Y.; Mohd Ali, A. R.; Maizan, M.; Sharifah, S. H.; Fauzia, O.; Kubo, M.; Aziz, A. J. (Springer, 2002)
A virus, named Oya virus, was isolated in Vero cell cultures from the lungs of a pig suspected of Nipah virus infection. The virus was revealed as a spherical enveloped RNA virus with a diameter of 79 nm. For identification of Oya virus, RT-PCR was performed. A common primer set for S-RNA of the Simbu serogroup of the genus Bunyavirus was able to amplify a cDNA from Oya virus RNA. The sequence data of the product revealed that the partial gene of Oya virus S-RNA segment had 65-70% homology with published cDNA sequences of Simbu serogroup viruses. The phylogenetic analysis of the data showed that the Oya virus is grouped in Simbu serogroup, but is genetically distinct from the serogroup viruses that have been analyzed molecularly. Serological surveys revealed that the virus distributed widely and densely in Malaysia.